Foreign capital vs. institutional and cultural conditions for the banking sector in Poland (Economic and Political Thought, 2016)
The Polish banking sector is dominated by foreign capital. The performanceand development of banks are determined by the institutional andcultural circumstances of the host country, i.e. Poland. Most of the foreignbank owners come from countries where the market economy has long traditionsand their societies are different in terms of perception and compliancewith law. Thus, the article focuses on the importance of these differences forthe development of the Polish banking sector. It also shows the main barriersand determinants related to the institutional and cultural context, includingregulations and governance issues, which foreign capital must deal with. Thepresented opinions are based on the available literature, reports and ownstudies – 59 interviews conducted among the managerial staff of banks withforeign capital (current and former board members, supervisory boards andmanaging directors), as well as representatives of banking supervision (membersof the Financial Supervision Commission).